Education and Training in Occupational Health Psychology: The Case for E-Learning - Houdmont, Jonathan; Leka, Stavroula; Cox, Tom (ISMAI Publishers, 2006)
For the discipline of occupational health psychology (OHP) to continue to evolve and to serve workers effectively it is imperative that education and training provision is available that enables students to acquire knowledge and skills, free of geographical and temporal constraints. This chapter begins with a brief introduction to the historical development of education and training in OHP in Europe. The review culminates with the assertion that higher education institutions are now required to act innovatively in regard to the expansion of provision. One such initiative involves the introduction of e-learning. A case study concerning the implementation of a Masters degree in OHP by e-learning is presented. On the outcomes of the case study, recommendations are offered for the design and implementation of such courses. The chapter concludes by raising some further questions that need to be addressed for education and training provision in OHP to continue to expand.